2007
DOI: 10.1002/jssc.200600534
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of gemcitabine in plasma and serum using reversed‐phase HPLC

Abstract: Gemcitabine (2'2'-difluorodeoxycytidine) is a pyrimidine analog used in the treatment of a variety of solid tumors. After intravenous (i.v.) administration, it is rapidly inactivated to 2'-deoxy-2',2'-difluorouridine (dFdU). A sensitive analytical method for the quantitation of gemcitabine is required for the assessment of alternative dosage and treatment schemes. A rapid and robust RP-HPLC assay for analysis of gemcitabine in human and animal plasma and serum was developed and validated using 2'-deoxyuridine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…[12,13] Hertel and colleagues performed hydrolytic transformation of the cytosine ring of gemcitabine (1) into the uracil ring, using acetic acid in aqueous solution. A lengthy multistep purification procedure was required, resulting in a 19 % yield.…”
Section: Chemistrymentioning
confidence: 99%
“…[12,13] Hertel and colleagues performed hydrolytic transformation of the cytosine ring of gemcitabine (1) into the uracil ring, using acetic acid in aqueous solution. A lengthy multistep purification procedure was required, resulting in a 19 % yield.…”
Section: Chemistrymentioning
confidence: 99%
“…Lanz et al . determined the LOD and LOQ of 10 ng/ml and 20 ng/ml, respectively, by using signal to noise ratio method [10]. While Xu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Very few HPLC methods deal with the determination of gemcitabine in the presence of degradation products from forced degradation studies, and those that do are time‐consuming, with complicated mobile phases and gradient elution leading to base line shifting [9,10]. To date, digestive enzymatic degradation studies of gemcitabine have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Isotype control AuNP-IgG-gemcitabine-mPEG (AIGP) nanoparticles were synthesized similarly by using isotype control human IgG in place of C225. Gemcitabine loading was determined by measuring unbound gemcitabine that was removed after filter centrifugation using reverse phase high performance liquid chromatography (HPLC) described elsewhere (14). Briefly, the UV absorbance of chromatographic peaks was recorded (Waters 1525 HPLC system, Milford, MA) at 275nm after separation through a Phenomenex Luna 5uC18(2) 100A column (250 x 4.6 mm, particle size 5 microns silica) using 0.1% TFA-water/acetonitrile at ambient temperature.…”
Section: Methodsmentioning
confidence: 99%